2012
DOI: 10.1002/lary.23298
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus DNA strongly correlates with a poorer prognosis in oral cavity carcinoma

Abstract: A high prevalence of hr and lr HPV infections was detected in the OSCC patients included in the study. Moreover, hr HPV positivity was correlated with a decreased 5-year disease-free survival rate compared with HPV- and lr HPV+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
76
4
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 47 publications
9
76
4
3
Order By: Relevance
“…In contrast to the clear picture in OPC [7,51,62], where the prognostic relevance of biologically active HPV infection is established, no such clear association has been found in OCSCC. Published literature is divided between the improved likelihood for HPV-positive OCSCC on one hand [63,64] and worst outcome on the other [65][66][67] with no clout on patient survival [10,37,68].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the clear picture in OPC [7,51,62], where the prognostic relevance of biologically active HPV infection is established, no such clear association has been found in OCSCC. Published literature is divided between the improved likelihood for HPV-positive OCSCC on one hand [63,64] and worst outcome on the other [65][66][67] with no clout on patient survival [10,37,68].…”
Section: Discussionmentioning
confidence: 99%
“…30 Three published studies report that HPV þ oral cavity squamous cell carcinoma are associated with poorer prognosis; two studies are from the same group in Taiwan and include an expanded cohort. [46][47][48] The strengths of the combined Taiwanese study are the large patient numbers and multivariate analysis; study weaknesses include the lack of p16 INK4a analysis and absence of validation for the HPV genotype data. The Taiwan study demonstrated an overall HPV prevalence of 21.2% among 410 patients; HPV16 was the most common subtype followed by HPV18.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, HPV was genotyped using only a blot hybridization assay, and not validated. 47 Duray et al 48 reported on 147 patients with oral cavity squamous cell carcinoma; HPV was detected by PCR with consensus and type-specific primers. HR-HPV was associated with decreased disease-free survival on KaplanMeier analysis; no multivariate analysis was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Cependant, les patients fumeurs HPV+ ont un moins bon pronostic que les patients HPV+ non fumeurs [22,23]. Quelques travaux, plus rares, ont trouvé une corrélation inverse entre une infection par HPV et la survenue d'une récidive ou la survie [24,25]. La surexpression de p16 par les cellules tumorales est aussi associée à un meilleur pronostic, même dans les tumeurs où une infection par HPV n'est pas retrouvée [26].…”
Section: Hpv Et Cancers Des Vads : Données Cliniquesunclassified